Thermochromic afterglow carbon dots and preparation method and application thereof
Patent Information
- Application Number
- CN202410591009.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-13
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2044-05-13
AI Technical Summary
然而,双模余辉仅在少数限域于刚性基质的CDs系统中实现
[0032] The beneficial effects of this invention are as follows: the afterglow carbon dots of this invention can achieve dual-mode afterglow of phosphorescence and thermally activated delayed fluorescence, with a photoluminescence quantum efficiency of up to 51% and an afterglow lifetime exceeding 0.3s. It can be applied to multiple fields such as water-based fluorescent inks, advanced information encryption and storage. Furthermore, the afterglow carbon dots of this invention can display different afterglow modes and colors at different temperatures, successfully achieving thermochromic afterglow. Moreover, they can be printed or applied to paper-based materials to achieve dual-mode afterglow, and the application method is simple and easy to operate.
Smart Images

Figure HDA0004837277670000011 
Figure HDA0004837277670000012 
Figure HDA0004837277670000021
Abstract
Description
Technical Field
[0001] This invention relates to the field of materials, specifically to a thermochromic afterglow carbon dot, its preparation method, and its application. Background Technology
[0002] Traditional inorganic afterglow materials rely on the unique electronic structures of rare earth elements and noble metal ions to promote spin-orbit coupling of room-temperature phosphorescence. However, the scarcity, high cost, and potential environmental toxicity of heavy metals remain unresolved issues. Organic afterglow materials have seen continuous development in recent years; however, they typically exhibit drawbacks such as poor photostability and complex synthesis processes, making them unsuitable for long-term information encryption.
[0003] Carbon dots (CDs) are a novel type of carbon-based nanomaterial that has attracted considerable attention due to their tunable optical properties, good photostability, low-cost synthesis, excellent biocompatibility, and non-toxicity. CD-based afterglow is becoming an active research area. Various afterglow properties have been demonstrated in many complex CD systems, such as excitation-dependent afterglow color and time-dependent dynamic afterglow color. Encapsulating CDs in organic or inorganic matrices is a widely adopted method for achieving room-temperature phosphorescence or thermally activated delayed fluorescence. However, dual-mode afterglow has only been achieved in a few CD systems confined to rigid matrices. The presence of these solid matrices, however, hinders the application of these materials as information encryption inks in paper printing. Summary of the Invention
[0004] In order to overcome at least one of the technical problems existing in the prior art, one of the objectives of the present invention is to provide a thermochromic afterglow carbon point.
[0005] The second objective of this invention is to provide a method for preparing thermochromic afterglow carbon dots.
[0006] The third objective of this invention is to provide an anti-counterfeiting ink.
[0007] The fourth objective of this invention is to provide an application of thermochromic afterglow carbon dots in the field of information encryption and storage.
[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0009] The first aspect of the present invention provides a thermochromic afterglow carbon dot, wherein the raw materials for preparing the afterglow carbon dot include a quinolone compound and a solid solvent, wherein the mass ratio of the quinolone compound to the solid solvent is 1:(1-300).
[0010] The afterglow carbon dots in this invention are afterglow luminescent materials. The characteristic of afterglow is that the light emission continues for a period of time after the excitation light source is turned off. In contrast, fluorescent luminescent materials emit light when excited by light, and the light emission disappears when the light source is turned off. Therefore, the afterglow carbon dots in this invention are not traditional fluorescent materials, but a novel afterglow carbon dot material that includes both fluorescent and afterglow luminescence.
[0011] Preferably, the mass ratio of the quinolone compound to the solid solvent is 1:(1-200); more preferably, the mass ratio of the quinolone compound to the solid solvent is 1:(1-100); even more preferably, the mass ratio of the quinolone compound to the solid solvent is 1:(1-20).
[0012] Preferably, the afterglow carbon dots have a carbon core with a graphene-like lattice.
[0013] Preferably, the particle size of the afterglow carbon dots is 1-10 nm; more preferably, the particle size of the afterglow carbon dots is 3-4 nm.
[0014] Preferably, the afterglow lifetime of the afterglow carbon point is greater than 0.3s.
[0015] Preferably, the afterglow carbon dots have a fluorescence emission peak A with a wavelength of 400-450 nm and a fluorescence emission peak B with a wavelength of 500-550 nm under an excitation light source of 300-400 nm; more preferably, the afterglow carbon dots have a fluorescence emission peak A with a wavelength of 420-440 nm and a fluorescence emission peak B with a wavelength of 500-520 nm under an excitation light source of 300-400 nm.
[0016] Preferably, the afterglow carbon dots exhibit blue delayed fluorescence afterglow at temperatures >70°C; the afterglow carbon dots exhibit yellow phosphorescent afterglow at temperatures <-20°C; and the afterglow carbon dots exhibit a cyan afterglow formed by a mixture of delayed fluorescence and phosphorescent dual-mode afterglow at temperatures between -20°C and 70°C. The afterglow carbon dots of this invention exhibit dual-mode afterglow emission at temperatures between -20°C and 70°C, namely phosphorescence and thermally activated delayed fluorescence. At temperatures >70°C, the emission mode of the afterglow carbon dots is thermally activated delayed fluorescence. At temperatures <-20°C, the emission mode of the afterglow carbon dots is phosphorescence. The afterglow carbon dots of this invention have dual-mode afterglow, that is, simultaneously exhibiting blue delayed fluorescence afterglow and yellow phosphorescent afterglow.
[0017] Quinolones are a class of commonly used broad-spectrum synthetic antibacterial drugs, named for the nitrogen-containing bicyclic heterocyclic structure they contain, which is the same as or similar to that of 4-quinolone.
[0018] Preferably, the quinolone compound is selected from at least one of levofloxacin, ofloxacin, norfloxacin, ciprofloxacin, fleroxacin, lomefloxacin, nafloxacin, pefloxacin, rufloxacin, balofloxacin, gapafloxacin, pazufloxacin, sparfloxacin, timafloxacin, clinfloxacin, gatifloxacin, moxifloxacin, sitafloxacin, prulifloxacin, besifloxacin, and delafloxacin.
[0019] Preferably, the solid solvent is selected from at least one of boric acid, metaboric acid, tetraboric acid, and boron trioxide.
[0020] The afterglow carbon dots in this invention are formed by carbonization and condensation reactions of quinolone compounds at high temperatures. They have a carbon core with a graphene-like lattice and a surface state covalently connected to conjugated segments of ofloxacin molecules. This results in the afterglow carbon dots exhibiting a fluorescence emission peak A with a wavelength of 400–450 nm and a fluorescence emission peak B with a wavelength of 500–550 nm under an excitation light source of 300–400 nm, corresponding to the carbon core and surface state, respectively. The size distribution of the afterglow carbon dots is uniform, approximately 1–10 nm.
[0021] The second aspect of the present invention provides a method for preparing the thermochromic afterglow carbon dots provided in the first aspect of the present invention, comprising the following steps:
[0022] A quinolone compound is mixed with a solid solvent, and then heated to react. The solid solvent is then removed to obtain the thermochromic afterglow carbon dots.
[0023] In this invention, the solid solvent melts during the heating reaction, and the quinolone compounds are dispersed and dissolved in the solid solvent and undergo carbonization condensation reaction to form luminescent carbon dots. Then the solid solvent is removed to obtain pure afterglow carbon dots.
[0024] Preferably, the heating temperature is 60–300°C and the heating time is 1–24 hours.
[0025] Preferably, the step of removing the solid solvent is: dialyzing for 12 to 96 hours using a dialysis bag with a molecular weight cutoff of 500 to 2000 Da.
[0026] Preferably, the preparation method further includes a freeze-drying step, which is performed after the step of removing the solid solvent.
[0027] A third aspect of the present invention is an anti-counterfeiting ink comprising the thermochromic afterglow carbon dots provided in the first aspect of the present invention. The anti-counterfeiting ink of the present invention can be printed onto a paper-based material via stamping or printing. The anti-counterfeiting pattern formed on the paper-based material has continuous luminescence, i.e., afterglow, after the excitation light source is turned off. Furthermore, the anti-counterfeiting pattern has different afterglow colors at different temperatures, i.e., it exhibits stable, dependent afterglow color change.
[0028] Preferably, the concentration of afterglow carbon dots in the anti-counterfeiting ink is 0.01–2 mg / mL.
[0029] Preferably, the anti-counterfeiting ink further includes a solvent.
[0030] Preferably, the solvent is water.
[0031] The fourth aspect of the present invention provides the application of the thermochromic afterglow carbon dots provided in the first aspect of the present invention in the field of information encryption and storage.
[0032] The beneficial effects of this invention are as follows: the afterglow carbon dots of this invention can achieve dual-mode afterglow of phosphorescence and thermally activated delayed fluorescence, with a photoluminescence quantum efficiency of up to 51% and an afterglow lifetime exceeding 0.3s. It can be applied to multiple fields such as water-based fluorescent inks, advanced information encryption and storage. Furthermore, the afterglow carbon dots of this invention can display different afterglow modes and colors at different temperatures, successfully achieving thermochromic afterglow. Moreover, they can be printed or applied to paper-based materials to achieve dual-mode afterglow, and the application method is simple and easy to operate.
[0033] The method for preparing afterglow carbon dots in this invention involves reacting quinolone compounds with a solid solvent under heating. The preparation method is simple and easy to operate, the raw materials are widely available, and the cost is low, making it suitable for mass industrial production. Attached Figure Description
[0034] Figure 1 This is a flowchart of the preparation process of the thermochromic afterglow carbon dots in Example 1.
[0035] Figure 2 The images shown are transmission electron microscope (TEM) images and high-resolution TEM images of the afterglow carbon dots prepared in Example 1.
[0036] Figure 3 This is an atomic force microscope image of the afterglow carbon dots prepared in Example 1.
[0037] Figure 4 The image shows the optical performance test results of the afterglow carbon dots prepared in Example 1.
[0038] Figure 5 The figures show the afterglow lifetime decay curves and fluorescence quantum efficiency test curves of CDs@Paper at wavelengths of 495nm and 560nm in this invention.
[0039] Figure 6 This is a test diagram of the thermochromic performance of CDs@Paper in this invention.
[0040] Figure 7 This is a test graph showing the linear relationship between the afterglow intensity ratio of the variable-temperature dual-mode CDs@Paper in this invention and temperature.
[0041] Figure 8 The image shows the temperature performance test results of the paper-based printing of afterglow carbon dots in Example 1.
[0042] Figure 9 This is a test diagram of the anti-counterfeiting application performance of the paper-based printing of afterglow carbon dots in Example 1. Detailed Implementation
[0043] The specific implementation of the present invention will be further described in detail below with reference to the accompanying drawings and examples, but the implementation and protection of the present invention are not limited thereto. It should be noted that any processes not specifically described in detail below are those that can be implemented or understood by those skilled in the art by referring to the prior art. Reagents or instruments used without specified manufacturers are all conventional products that can be purchased commercially.
[0044] In some embodiments of the present invention, a thermochromic afterglow carbon dot is provided. The raw materials for preparing the afterglow carbon dot include a quinolone compound and a solid solvent, with a mass ratio of quinolone compound to solid solvent of 1:(1-300). The afterglow carbon dot in the present invention is a conjugated core formed by the carbonization and condensation of quinolone compound molecules at high temperatures (e.g., 100-300°C), and fragments of quinolone compound molecules are covalently linked to the surface. The inventors discovered that when energy transfer occurs between the carbonized conjugated domain and the surface-conjugated molecular fragments of the carbon dot, the band gap of the excited singlet and triplet states can be narrowed, generating effective intersystem crossing and anti-intersystem crossing, thereby realizing dual-mode afterglow in a single carbon dot material.
[0045] In some embodiments of the present invention, the mass ratio of the quinolone compound to the solid solvent is 1:(1-20).
[0046] In some embodiments of the present invention, the afterglow carbon dots have a carbon core with a graphene-like lattice.
[0047] In some embodiments of the present invention, the particle size of the afterglow carbon dots is 1 to 10 nm; more preferably, the particle size of the afterglow carbon dots is 3 to 4 nm.
[0048] In some embodiments of the present invention, the afterglow lifetime of the afterglow carbon dots is greater than 0.3s.
[0049] In some embodiments of the present invention, the afterglow carbon dots have a fluorescence emission peak A with a wavelength of 400-450 nm and a fluorescence emission peak B with a wavelength of 500-550 nm under an excitation light source of 300-400 nm; more preferably, the afterglow carbon dots have a fluorescence emission peak A with a wavelength of 420-440 nm and a fluorescence emission peak B with a wavelength of 500-520 nm under an excitation light source of 300-400 nm.
[0050] In some embodiments of the present invention, the afterglow carbon dots exhibit blue delayed fluorescence afterglow at temperatures >70°C; yellow phosphorescent afterglow at temperatures <-20°C; and cyan afterglow formed by a mixture of delayed fluorescence and phosphorescent dual-mode afterglow at temperatures between -20°C and 70°C. The afterglow carbon dots of the present invention exhibit dual-mode afterglow luminescence at temperatures between -20°C and 70°C, namely phosphorescence and thermally activated delayed fluorescence. At temperatures >70°C, the afterglow carbon dots exhibit blue thermally activated delayed fluorescence. At temperatures <-20°C, the afterglow carbon dots exhibit yellow phosphorescence.
[0051] Quinolones are a class of commonly used broad-spectrum synthetic antibacterial drugs, named for containing a nitrogen-containing bicyclic heterocyclic structure similar to or the same as that of 4-quinolones. In some embodiments of the present invention, the quinolone compound may be a carboxyl or amino derivative derived from a nitrogen-containing bicyclic heterocycle as the parent nucleus, and the quinolone compound may be selected from at least one of compounds derived from a 1,8-naphthyl-4-one parent nucleus. In some embodiments of the present invention, the quinolone compound is selected from at least one of levofloxacin, ofloxacin, norfloxacin, ciprofloxacin, fleroxacin, lomefloxacin, nafloxacin, pefloxacin, rufloxacin, balofloxacin, gapafloxacin, pazufloxacin, sparfloxacin, timafloxacin, clinfloxacin, gatifloxacin, moxifloxacin, sitafloxacin, prulifloxacin, besifloxacin, and derafloxacin. In some embodiments of the present invention, the quinolone compound is levofloxacin. In other words, quinolone compounds can be selected not only individually, but also in combination of several. That is to say, as long as a quinolone compound is carbonized and condensed to form a carbon dot with a carbonized conjugated core and covalently linked molecular fragments, and can achieve dual-mode afterglow, then the selection or combination of quinolone compounds and their carboxyl and amino derivatives that meet the above conditions are within the scope of protection mentioned above.
[0052] In some embodiments of the present invention, the solid solvent is selected from at least one of boric acid, metaboric acid, tetraboric acid, and boron trioxide.
[0053] The afterglow carbon dots in this invention are formed by carbonization and condensation reactions of quinolone compounds at high temperatures. They have a carbon core with a graphene-like lattice and a surface state covalently connected to conjugated segments of ofloxacin molecules. This results in the afterglow carbon dots exhibiting a fluorescence emission peak A with a wavelength of 400–450 nm and a fluorescence emission peak B with a wavelength of 500–550 nm under an excitation light source of 300–400 nm, corresponding to the carbon core and surface state, respectively. The size distribution of the afterglow carbon dots is uniform, approximately 1–10 nm.
[0054] In some embodiments of the present invention, the present invention also provides a method for preparing the above-mentioned thermochromic afterglow carbon dots, comprising the following steps:
[0055] Quinolone compounds are mixed with a solid solvent, then heated to react, and the solid solvent is removed to obtain thermochromic afterglow carbon dots.
[0056] The preparation method in this invention can obtain bimodal afterglow carbon dots by selecting different quinolone compounds as reactants, thus expanding the source of raw materials, reducing costs, and promoting the information encryption and storage applications of bimodal afterglow carbon dots. Through long-term research and practice, the inventors creatively discovered that during the solid-state heating preparation of carbon dots under environmental pressure, quinolone compounds as precursors can undergo carbonization and condensation under heating conditions to form a conjugated core, with fragments of quinolone compound molecules covalently linked to the surface. Energy transfer exists between the carbonization conjugated domain and the surface-conjugated molecular fragments of the carbon dot, narrowing the band gap of the excited singlet and triplet states, generating effective intersystem crossing and anti-intersystem crossing, thereby achieving bimodal afterglow in a single carbon dot material.
[0057] In this invention, the solid solvent melts during the heating reaction, and the quinolone compounds are dispersed and dissolved in the solid solvent and undergo carbonization condensation reaction to form luminescent carbon dots. Then the solid solvent is removed to obtain pure afterglow carbon dots.
[0058] In some embodiments of the present invention, the heating temperature is 60–300°C, for example, 60°C, 65°C, 70°C, 75°C, 80°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 165°C, 170°C, 175°C, 180°C, 1 Temperatures range from 85℃, 190℃, 195℃, 200℃, 210℃, 220℃, 230℃, 240℃, and 250℃, with heating times from 1 to 24 hours, such as 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, 13 hours, 14 hours, 15 hours, 16 hours, 17 hours, 18 hours, 19 hours, 20 hours, 21 hours, 22 hours, 23 hours, or 24 hours.
[0059] In some embodiments of the present invention, the step of removing the solid solvent is as follows: dialyzing for 12 to 96 hours using a dialysis bag with a molecular weight cutoff of 500 to 2000 Da.
[0060] In some embodiments of the present invention, the preparation method further includes a freeze-drying step, which is performed after the step of removing the solid solvent.
[0061] In some embodiments of the present invention, an anti-counterfeiting ink is also provided, comprising the aforementioned thermochromic afterglow carbon dots. The anti-counterfeiting ink of the present invention can be printed onto paper-based materials via stamping or printing. The anti-counterfeiting pattern formed on the paper-based material continues to emit light, i.e., afterglow, after the excitation light source is turned off. Furthermore, the anti-counterfeiting pattern has different afterglow colors at different temperatures, i.e., it exhibits stable afterglow color change.
[0062] In some embodiments of the present invention, the concentration of afterglow carbon dots in the anti-counterfeiting ink is 0.01 to 2 mg / mL.
[0063] In some embodiments of the present invention, the anti-counterfeiting ink also includes a solvent.
[0064] In some embodiments of the present invention, the solvent is water.
[0065] The thermochromic afterglow carbon dots in this invention can be applied in the fields of information encryption and storage.
[0066] The specific implementation of the present invention will be further described in detail below with reference to specific embodiments.
[0067] Example 1
[0068] Reference Figure 1 The process flow diagram in the image illustrates a method for preparing paper-based printable dual-mode thermochromic afterglow carbon dots, comprising the following steps:
[0069] Levofloxacin (0.15 g) and boric acid (2.50 g) were mixed in an open beaker and then placed in a high-temperature oven at 200°C for 3 hours. After the reaction was complete, a yellow glassy solid (as shown in the image) was obtained in the beaker. Figure 1 (Image under fluorescent light). Dissolve it in water to obtain a clear yellow-green solution. Then dialyze the carbon dot solution for 36 hours using a dialysis bag with a molecular weight cutoff of 500 Da to remove boric acid. After dialysis, freeze-dry the pure carbon dot solution in the dialysis bag to obtain a brown solid, thus preparing the paper-printable dual-mode thermochromic afterglow carbon dots in this example.
[0070] Example 2
[0071] The only difference between the paper-based printable dual-mode thermochromic afterglow carbon dot preparation method in this example and Example 1 is that the mass of levofloxacin in this example is 0.2g.
[0072] Example 3
[0073] The method for preparing the paper-based printable dual-mode thermochromic afterglow carbon dots in this example differs from that in Example 1 only in that the mass of levofloxacin in this example is 0.25g.
[0074] Example 4
[0075] The only difference between the paper-based printable dual-mode thermochromic afterglow carbon dot preparation method in this example and Example 1 is that the mass of levofloxacin in this example is 0.50g.
[0076] Example 5
[0077] The only difference between the paper-based printable dual-mode thermochromic afterglow carbon dot preparation method in this example and Example 1 is that the mass of levofloxacin in this example is 1g.
[0078] Example 6
[0079] The method for preparing the paper-based printable dual-mode thermochromic afterglow carbon dots in this example differs from that in Example 1 only in that the mass of levofloxacin in this example is 1.5g.
[0080] Example 7
[0081] The only difference between the paper-based printable dual-mode thermochromic afterglow carbon dot preparation method in this example and Example 1 is that the reaction temperature in this example is 160°C.
[0082] Example 8
[0083] The only difference between the paper-based printable dual-mode thermochromic afterglow carbon dot preparation method in this example and Example 1 is that the reaction temperature in this example is 180°C.
[0084] Example 9
[0085] The only difference between the paper-based printable dual-mode thermochromic afterglow carbon dot preparation method in this example and Example 1 is that the reaction temperature in this example is 220°C.
[0086] Example 10
[0087] The only difference between the paper-based printable dual-mode thermochromic afterglow carbon dot preparation method in this example and Example 1 is that the reaction temperature in this example is 240°C.
[0088] Performance testing
[0089] (1) Microscopic morphology characterization
[0090] The morphology of the afterglow carbon dots prepared in Example 1 was tested using transmission electron microscopy and high-resolution transmission electron microscopy. The specific test results are as follows: Figure 2 As shown, where, Figure 2 (a) is an HRTEM image of the afterglow carbon dots prepared in Example 1. Figure 2 (b) is a TEM image of the afterglow carbon dots prepared in Example 1. Figure 2 (a) It can be seen that the afterglow carbon dots have graphene-like lattice fringes with a lattice spacing of 0.24 nm, corresponding to the (1120) crystal plane of graphene. Figure 2 (b) It can be seen that the afterglow carbon dots are evenly distributed and have a particle size of 3-4 nm.
[0091] The height of the dual-mode afterglow carbon dots obtained in Example 1 was measured using atomic force microscopy (AFM), and the test results are as follows: Figure 3 As shown. By Figure 3 It can be seen that the height distribution of the afterglow carbon dots is uniform, with an average height of about 1.8 nm.
[0092] (2) Optical performance testing
[0093] The aqueous solution of the dual-mode afterglow carbon dots obtained in Example 1 was characterized by spectroscopic analysis. The specific test results are as follows: Figure 4 As shown. Among them, Figure 4 a represents the UV-Vis absorption and fluorescence emission spectra of the dual-mode afterglow carbon dot aqueous solution in Example 1. Figure 4 As can be seen from a, the afterglow carbon dots have a broad absorption peak in the ultraviolet to visible light region, and the main emission peak is located at 510 nm. Figure 4 b is the excitation-emission three-dimensional mapping of the dual-mode afterglow carbon dot aqueous solution in Example 1, derived from... Figure 4 As shown in b, the main peak of the afterglow carbon point is located at 510 nm, which corresponds to the light emission spectrum of the carbonized core (carbon nucleus state). The weak luminescence center at 430 nm corresponds to the levofloxacin molecular fragment (molecular state) covalently linked to the carbon point surface. Figure 4 c represents the excitation spectrum of the dual-mode afterglow carbon dot aqueous solution in Example 1 at 510 nm and 430 nm, derived from... Figure 4 c indicates that the excitation spectrum at 510 nm shows a newly added, expanded conjugate domain π-π* excitation peak located at 290 nm. Figure 4 d represents the fluorescence decay curves of the dual-mode afterglow carbon dot aqueous solution at 510 nm and 430 nm in Example 1. Figure 4 As can be seen from d, in the initial stage, the intensity at 430nm decreases sharply while the intensity at 510nm increases, indicating that there is an energy transfer between the molecular state corresponding to 430nm and the carbon nucleus state corresponding to 510nm.
[0094] (3) Thermochromic performance test
[0095] The aqueous solution (1 mg / mL) of the dual-mode afterglow carbon dots obtained in Example 1 was used as ink to print CDs@Paper on filter paper. The afterglow lifetime and fluorescence quantum yield at wavelengths of 495 nm and 560 nm were tested, and the specific test results are as follows: Figure 5 As shown, where, Figure 5a is the afterglow lifetime decay curve of CDs@Paper at wavelengths of 495nm and 560nm. Figure 5 b shows the fluorescence quantum efficiency curves of CDs@Paper at wavelengths of 495 nm and 560 nm. Figure 5 As can be seen from a, the afterglow lifetimes of CDs@Paper are 0.32s (at 495nm) and 0.39s (at 560nm), respectively. Figure 5 As shown in b, the photoluminescence quantum efficiency of CDs@Paper is as high as 51%.
[0096] The afterglow spectrum of the CDs@Paper obtained above was tested, and the specific test results are as follows: Figure 6 As shown, where, Figure 6 a is the three-dimensional mapping spectrum of the excitation afterglow emission of CDs@Paper. As can be seen from the figure, CDs@Paper has an excitation-independent afterglow emission spectrum. Figure 6 Figure b shows the afterglow emission spectra of CDs@Paper at different temperatures (403K to 193K, in 30K increments). As can be seen, at high temperature (430K), the main peak of the afterglow emission spectrum of CDs@Paper is located near 480nm, indicating thermally activated delayed fluorescence (TRF). As the temperature decreases, the main peak of the afterglow emission spectrum continuously redshifts, and the afterglow mode gradually shifts towards phosphorescence. At low temperature (193K), the main afterglow peak is at 560nm, indicating phosphorescence. Figure 6 c is the CIE 1931 color coordinate diagram corresponding to the temperature-dependent afterglow emission spectrum of CDs@Paper. As can be seen from the diagram, as the temperature changes from 193K to 403K, the color of the afterglow spectrum of CDs@Paper changes from yellow to blue.
[0097] The intensity ratio of the temperature-dependent dual-mode afterglow of CDs@Paper was tested and correlated with temperature. Specific test results are as follows: Figure 7 As shown, where, Figure 7 In the figure, line a represents the intensity ratio of the afterglow spectrum at 560 nm and 475 nm under excitation by 395 nm excitation light (I). 560 / I 475 The linear relationship between K and temperature (223-313 K) is given by y = 17.04 - 0.05x, where x is temperature and y is K. 560 / I 475 Ratio; Line b represents the intensity ratio of the afterglow spectrum at 560 nm and 475 nm under 365 nm excitation light (I 560 / I 475 The linear relationship between K and temperature (313-403 K) is given by y = 11.51 - 0.03x, where x is temperature and y is K. 560 / I 475 Ratio. From Figure 7 It can be seen that CDs@Paper has good temperature sensing capability in a wide range of 223K to 403K.
[0098] (4) Temperature variation and encryption performance test after paper-based printing
[0099] Using the aqueous solution (1 mg / mL) of the dual-mode afterglow carbon dots obtained in Example 1 as ink, the words "University of Macau" were printed on filter paper. Figure 8 As shown, where, Figure 8 'a' is a schematic diagram showing the printing of the words "University of Macau" on filter paper using an aqueous solution of the dual-mode afterglow carbon dots from Example 1 as ink. Figure 8 b uses an aqueous solution of the dual-mode afterglow carbon dots from Example 1 as ink to print the color-changing afterglow images of the words "University of Macau" on filter paper at different temperatures. Figure 8 It can be seen that the dual-mode afterglow carbon dots in Example 1 can be used as ink for paper-based printing, and have high clarity and afterglow luminescence performance during printing.
[0100] An aqueous solution (1 mg / mL) of the dual-mode afterglow carbon dots obtained in Example 1 and single-mode phosphorescent CDs (P-CDs, described in K. Jiang, Y. Wang, C. Cai, H. Lin, Adv. Mater. 2018, 30, 1800783) were used as inks to print 3D codes on filter paper. Their anti-counterfeiting performance at different temperatures was then tested. Figure 9 As shown. Figure 9Using an aqueous solution of the dual-mode afterglow carbon dots from Example 1 of this invention as ink, 3D codes with fluorescence at 298K and different afterglow colors at 193K, 298K, and 393K were printed on filter paper. Single-mode phosphorescent CDs (P-CDs) and the dual-mode afterglow carbon dots obtained in Example 1 were used as ink to print 3D code patterns in various regions. The obtained 3D encoded patterns, under ultraviolet light excitation at room temperature, showed blue fluorescence from the P-CDs and cyan fluorescence from the prepared CDs. The combined fluorescence pattern is designated as code 1, containing information A. When the excitation light is turned off, the P-CDs region emits deep green phosphorescence, while the prepared CDs region emits cyan dual-mode afterglow, forming a pattern of colored afterglow, designated as code 3, containing information C. When the temperature is cooled to 193K, the phosphorescence of the P-CDs region remains unchanged, while the dual-mode afterglow of the dual-mode afterglow CDs region obtained in Example 1 turns into yellow phosphorescence, producing a pattern of colored afterglow, designated as code 2, containing information B. When the temperature rises to 393K, the phosphorescence in the P-CDs region disappears, leaving only the blue thermally activated delayed fluorescence in the CDs region of the dual-mode afterglow carbon dots obtained in Example 1. This colored afterglow pattern corresponds to code 4, containing information D. Therefore, the afterglow carbon dots with thermochromic afterglow properties on paper-based printable 3D codes in Example 1 demonstrate a significant advantage in constructing advanced information encryption.
[0101] Tests showed that the afterglow carbon dots in Examples 2-10 had essentially the same performance as the afterglow carbon dots in Example 1.
[0102] In summary, during solid-state heating, this invention involves the carbonization and condensation of quinolone molecules to form a carbon core (carbon core state) with a graphene-like lattice. Fragments of quinolone molecules (surface state) are covalently bonded to the carbon dot surface. Energy transfer between the carbon core and surface states promotes the generation of thermally activated delayed fluorescence. The afterglow carbon dots in this invention are made from widely available, inexpensive raw materials, and easy to promote and apply. As a novel type of paper-printable carbon dot with dual-mode afterglow, it has been successfully applied to paper to achieve dual-mode afterglow, thus enabling thermochromic afterglow for use in high-level information encryption and storage.
[0103] The embodiments of the present invention have been described in detail above. However, the present invention is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of the present invention. Furthermore, the embodiments of the present invention and the features thereof can be combined with each other unless otherwise specified.
Claims
1. A thermochromic afterglow carbon dot, characterized in that: The raw materials for preparing the afterglow carbon dots are quinolone compounds and solid solvents, wherein the mass ratio of the quinolone compound to the solid solvent is 1:(1~300); the solid solvent is boric acid, and the quinolone compound is levofloxacin; the thermochromic afterglow carbon dots are prepared by a method including the following steps: A quinolone compound is mixed with a solid solvent, and then heated to react. The solid solvent is then removed to obtain the thermochromic afterglow carbon dots. The heating temperature is 160~300℃ and the heating time is 3~24h.
2. The thermochromic afterglow carbon dot according to claim 1, characterized in that: The afterglow carbon dots have a carbon core with a graphene-like lattice. And / or, the particle size of the afterglow carbon dots is 1~10nm; And / or, the afterglow lifetime of the afterglow carbon dots is greater than 0.3s.
3. The thermochromic afterglow carbon dot according to claim 1, characterized in that: The afterglow carbon dots exhibit a fluorescence emission peak A with a wavelength of 400-450 nm and a fluorescence emission peak B with a wavelength of 500-550 nm under an excitation light source of 300-400 nm.
4. The thermochromic afterglow carbon dot according to claim 1, characterized in that: The afterglow carbon dots exhibit blue delayed fluorescence afterglow at temperatures >70℃; the afterglow carbon dots exhibit yellow phosphorescent afterglow at temperatures <-20℃; and the afterglow carbon dots exhibit cyan afterglow formed by a mixture of delayed fluorescence and phosphorescent dual-mode afterglow at temperatures between -20℃ and 70℃.
5. The thermochromic afterglow carbon dot according to claim 1, characterized in that: The step of removing the solid solvent is as follows: dialyze for 12 to 96 hours using a dialysis bag with a molecular weight cutoff of 500 to 2000 Da.
6. An anti-counterfeiting ink, characterized in that: Includes the thermochromic afterglow carbon dots as described in any one of claims 1 to 5.
7. The anti-counterfeiting ink according to claim 6, characterized in that: The concentration of afterglow carbon dots in the anti-counterfeiting ink is 0.01~2 mg / mL.
8. The application of the thermochromic afterglow carbon dots according to any one of claims 1 to 5 in the field of information encryption and storage.
Citation Information
Patent Citations
Room-temperature phosphorescent afterglow luminescent carbon quantum dot as well as solid-phase one-step preparation method and application thereof
CN115806819A